Aging damage mechanism and mechanical properties degradation of 3D orthogonal woven thermoset composites subjected to cyclic hygrothermal environment. (October 2022) - Deng, Kelin; Cheng, Hui; Suo, Haoyuan; Liang, Biao; Li, Yuan; Zhang, Kaifu
Highlights: Accelerated cyclic hygrothermal aging tests are carried out. Tg of 3DOWCs rises and mechanical properties decrease after cyclic hygrothermal aging. Warp yarn direction of 3DOWCs is more susceptible to environmental aging than the weft yarn direction. Fracture analysis proves that interface debonding, cracks, and embrittlement of fiber bundles are the primary reasons for the property degradation. Abstract: 3D orthogonal woven thermoset composites (3DOWCs) can be applied to fabricate the bearing structures of supersonic aircrafts due to their excellent mechanical properties. However, 3DOWCs would be subjected to the cyclic hygrothermal aging caused by the specific service environment of supersonic aircrafts. This paper aims to reveal the cyclic hygrothermal aging mechanism and the consequent degradations of mechanical properties of 3DOWCs. Accelerated hygrothermal cyclical ageing tests were carried out in a simulated service environment of supersonic aircrafts. The aging damage mechanisms were investigated with moisture content monitoring, micromorphology observation and Fourier transform infrared (FTIR) analysis. The evolution of mechanical properties was evaluated by quasi-static mechanical tests (tension, compression and interlaminar shear) and Dynamic mechanical analysis (DMA). The results show that the mechanical properties of 3DOWCs deteriorate significantly with the increasing of hygrothermal aging cycle. Interface debonding, crack propagation, and embrittlement of fiber bundles are the main reasons of the degradation.